Numerical modelling of microscopic lubricant flow in sheet metal forming. Application to plane strip drawing. (14th February 2017) - Carretta, Y.; Boman, R.; Bech, J.; Legrand, N.; Laugier, M.; Ponthot, J.‐P.
Summary: This paper presents a numerical investigation of microscopic lubricant flows from the cavities to the plateaus of the surface roughness of metal sheets during forming processes. This phenomenon, called micro‐plasto‐hydrodynamic lubrication, was observed experimentally in various situations such as compression sliding tests, strip drawing and cold rolling. It leads to local friction drop and wear reduction. It is therefore critical to achieve a good understanding of this phenomenon. As to move towards that goal, a multiscale fluid–structure interaction model is developed to model lubricant flows at the microscopic scale. These simulations are made possible through the use of the Arbitrary Lagrangian Eulerian (ALE) formalism. In this paper, this methodology is used to study plane strip drawing. The numerical model is able to predict the onset of lubricant escape and the amount of lubricant flowing on the plateaus. Numerical results exhibit good agreement with experimental measurements. Copyright © 2017 John Wiley & Sons, Ltd.